2022
DOI: 10.1002/acm2.13879
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscopic biodosimetry using plasmid DNA in radiotherapy with metallic nanoparticles

Abstract: Nanoscopic lesions (complex damages), are the most lethal lesions for the cells. As nanoparticles have become increasingly popular in radiation therapy and the importance of analyzing nanoscopic dose enhancement has increased, a reliable tool for nanodosimetry has become indispensable. In this regard, the DNA plasmid is a widely used tool as a nanodosimetry probe in radiobiology and nano‐radiosensitization studies. This approach is helpful for unraveling the radiosensitization role of nanoparticles in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 132 publications
0
3
0
Order By: Relevance
“…In addition spectroscopy of metallic nanoparticles showed that large number of secondary electrons generated from photon and nanoparticle interactions, are Auger electrons [ 6 , 71 ]. These electrons could induce single strand breaks and double strand breaks to the DNA molecules directly or could indirectly increase ROS production leading to DNA damage and cell death [ 72 ]. So the coating layer could affect the number of Auger electrons reach to the tumor cells in the vicinity of metallic nanoparticles and influence the radiosensitization properties of nanoparticles Due to the low atomic number of common coating layers and the dominance of photoelectric effect in this energy range, there is little expectation for the coating layer to interact with the photon beams and involve in physical dose enhancement.…”
Section: Physical Enhancementmentioning
confidence: 99%
“…In addition spectroscopy of metallic nanoparticles showed that large number of secondary electrons generated from photon and nanoparticle interactions, are Auger electrons [ 6 , 71 ]. These electrons could induce single strand breaks and double strand breaks to the DNA molecules directly or could indirectly increase ROS production leading to DNA damage and cell death [ 72 ]. So the coating layer could affect the number of Auger electrons reach to the tumor cells in the vicinity of metallic nanoparticles and influence the radiosensitization properties of nanoparticles Due to the low atomic number of common coating layers and the dominance of photoelectric effect in this energy range, there is little expectation for the coating layer to interact with the photon beams and involve in physical dose enhancement.…”
Section: Physical Enhancementmentioning
confidence: 99%
“…The past decades have witnessed the successful marriage of medical science and nanotechnology, propelling the functional nanomaterials as clinical candidates for cancer theranostics. High- Z metal element contained nanomaterials could act as effective radiosensitizers to increase the local absorption of the incident X-ray energy in tumors, achieving low-dose induced irreparable DNA lesions or radioresistance reversal. Among them, the hafnium oxide (HfO 2 )-contained nanosized radiosensitizer, commercially named as NBTXR3 or Hensify, is undoubtedly the shining one, which has been approved by European marketing for advanced soft tissue sarcoma, granted with fast track designation (FTD) by FDA for locally advanced head and neck squamous cell carcinoma, and currently applied for many other solid tumors in clinical trials. In addition, NBTXR3-meidated radiosensitization could increase the production of cytosolic dsDNA to facilitate the activation of cGAS-STING pathway. To ensure efficient STING pathway activation, various TME-responsive manganese (Mn)-based nanomaterials were developed as STING nanoagonists since Mn 2+ was essential to cGAS-STING activation.…”
Section: Introductionmentioning
confidence: 99%
“…An assay based on DNA degradation was used for systematic studies (Figure 1). [49] Figure 1: Schematic figure of surfactant-free PtNP generation through laser ablation in liquids with an IR-laser (left). After the addition of one ligand species forming PtNP with ligand, the particles are irradiated with protons in phosphate buffer saline (PBS) in the presence of plasmid DNA.…”
Section: Introductionmentioning
confidence: 99%